Maximising energy recovery from the brewery wastewater treatment system: a study evaluating the anaerobic digestion wastewater treatment plant at SAB's newlands brewery - Nkadimeng, Lefa Steven (Centre for Bioprocess Engineering Research, 2015)
Includes bibliography.